Anatomy of style : figure drawing techniques - Jones, Patrick J.; Wilshire, Pat (London : Korero Books, 2016)
Much more than a book on anatomy: this guide explains how to use knowledge of the human form to produce drawings with style and grace, using pastel, pencil, and charcoal techniques and tools. It features reproductions of the original anatomy sheets and figure drawings produced during Patrick's live lectures, and is packed full of insights from a modern master of anatomy. Offering plenty of practical instruction and insights for digital painters, this resource will also enhance the drawing and painting techniques of figurative artists, animators, and students at every level of experience.
Keywords: Anatomy, Artistic; Human figure in art; Human anatomy; Drawing -- Technique; Painting -- Technique